N-linked glycosylation of PD-L1/PD-1: an emerging target for cancer diagnosis and treatment - Zhiyun Duan; Runhan Shi; Bo Gao; Jiabin Cai (Journal of Translational Medicine, 2024)
Abstract During tumorigenesis and progression, the immune checkpoint programmed death-1 (PD-1) and its ligand programmed death ligand-1 (PD-L1) play critical roles in suppressing T cell-mediated anticancer immune responses, leading to T-cell exhaustion and subsequent tumor evasion. Therefore, anti-PD-L1/PD-1 therapy has been an attractive strategy for treating cancer over the past decade. However, the overall efficacy of this approach remains suboptimal, revealing an urgent need for novel insights. Interestingly, increasing evidence indicates that both PD-L1 on tumor cells and PD-1 on tumor-specific T cells undergo extensive N-linked glycosylation, which is essential for the stability and interaction of these proteins, and this modification promotes tumor evasion. In various preclinical models, targeting the N-linked glycosylation of PD-L1/PD-1 was shown to significantly increase the efficacy of PD-L1/PD-1 blockade therapy. Furthermore, deglycosylation of PD-L1 strengthens the signal intensity in PD-L1 immunohistochemistry (IHC) assays, improving the diagnostic and therapeutic relevance of this protein. In this review, we provide an overview of the regulatory mechanisms underlying the N-linked glycosylation of PD-L1/PD-1 as well as the crucial role of N-linked glycosylation in PD-L1/PD-1-mediated immune evasion. In addition, we highlight the promising implications of targeting the N-linked glycosylation of PD-L1/PD-1 in the clinical diagnosis and treatment of cancer. Our review identifies knowledge gaps and sheds new light on the cancer research field.